Impact of chromatic and modal dispersion on frequency response of optical multimode fibers - Mrabet, Hichem; Dayoub, Iyad; Attia, Rabah; AL-Holou, Nizar; Tatkeu, Charles (2009 IEEE Symposium on Computers and Communications, 2009)
In this work, we have studied chromatic and modal dispersion of silica graded-index optical fibers as a function of mode depending parameters and a launching condition in local area network (LAN) context. We have investigated mode-depending parameters, namely modal delay, modal attenuation and mode-coupling effects as a function of wavelength. We have proved that the number of excited mode groups depend on spot radius beam when the fiber is excited with a Gaussian input beam. On the other hand, we have demonstrated that we can get a good frequency response of system with a proper wavelength value and under an optimal launching condition in order to decrease the modal dispersion effects of multimode optical fiber. Finally, we have investigated the transfer function of MMF with taking into account chromatic and modal dispersion and considering two structured of studied optical fiber.